Avaliação cefalométrica do efeito do tratamento da má oclusão Classe II, divisão 1, com o bionator de Balters: estudo com implantes metálicos - Melo, Ana Cláudia Moreira; Gandini Jr., Luiz Gonzaga [UNESP]; Santos-pinto, Ary Dos [UNESP]; Araújo, Adriano Marotta [UNESP]; Gonçalves, João Roberto [UNESP] (Dental Press Editora, 2006)
AIM: to evaluate the bionator treatment effect on Class II, division 1, malocclusion, presenting mandibular retrusion or mandibular length deficiency. METHODS: it is described the effects of the treatment in three patients that were accompanied with no treatment for one year and them were treated for two years with bionator. In all three patients metallic implants were inserted to serve as reference to cephalometric tracing superimposition that, together with some traditional cephalometric measurements, generated data to the evaluation of the orthopedic and orthodontic effects of Class II malocclusion treatment with this appliance. RESULTS AND CONCLUSIONS: it was observed a maxillary growth restriction and a stimulus of mandibular growth as well as a change in the direction of condylar growth. There was also an uprighting of the upper incisors and in the lower arch Balters bionator increased the natural tendency of buccal movement of the incisors.

OBJETIVOS: julgamento descritivo dos efeitos do bionator no tratamento da má oclusão Classe II, divisão 1, quando está presente uma retrusão mandibular ou uma deficiência do crescimento mandibular. METODOLOGIA: são apresentados os resultados do tratamento em três pacientes que foram acompanhados sem tratamento por um período de um ano e, posteriormente, tratados com o bionator por um período de dois anos. Em todos os pacientes foram inseridos implantes metálicos que serviram como referência para as sobreposições dos traçados cefalométricos que, em conjunto com algumas medidas cefalométricas tradicionais, geraram dados para a avaliação do efeito ortopédico e ortodôntico do tratamento da má oclusão Classe II com este aparelho. RESULTADOS E CONCLUSÕES: foi observada uma restrição do crescimento da maxila e um estímulo do crescimento da mandíbula, assim como alteração na direção do crescimento condilar. Foi também observada uma verticalização dos incisivos superiores e, no arco inferior, aumento na tendência natural de vestibularização dos incisivos inferiores.
Cephalometric evaluation of Class II division 1 malocclusion treatment with Balters bionator: study with metallic implants
Keywords: Cephalometrics; Class II division 1; Balters bionator; Cefalometria; Classe II, divisão 1; Bionator de Balters